The Impact of Globalization on the Rate of E-waste Recycling: Evidence From European Countries - Rasim Yilmaz; Cuneyt Koyuncu (Amfiteatru Economic)
for the implementation of the circular economy and the reduce-reuse-recycle paradigm envisaged by the EU and UNDP. Since the rate of e-waste recycling is one of the most important indicators of the circular economy, it is necessary to identify the factors that affect it, and to determine the degree to which these factors influence it in order to foster e-waste recycling. Using the panel quantile regression technique on panel data including 30 European countries (EU28+2) and the time period from 2008 to 2018, this study analyses the effects of overall globalization and its three sub-dimensions (economic, political, and social globalization) on the rate of e-waste recycling. The results indicate that overall globalization and its three sub-dimensions have a positive impact on the rate of e-waste recycling in 30 European countries (EU28+2) during the estimation period, thus contributing to the circular economy. Therefore, supporting all aspects of globalization (economic, political, and social) will enhance the circular economy.